2024
DOI: 10.3847/2041-8213/ad1d61
|View full text |Cite
|
Sign up to set email alerts
|

Delayed and Fast-rising Radio Flares from an Optical and X-Ray-detected Tidal Disruption Event in the Center of a Dwarf Galaxy

Fabao Zhang,
Xinwen Shu,
Lei Yang
et al.

Abstract: AT 2018cqh is a unique tidal disruption event (TDE) discovered in a dwarf galaxy. Both the light-curve fitting and galaxy scaling relationships suggest a central black hole mass in the range of 5.9 < logM BH/M ☉ < 6.4. The r-band peak luminosity is ∼ 1043 erg s−1, making AT 2018cqh relatively faint among known optical TDEs. A delayed X-ray brightening was found around 590 days after the optical discovery but shows an unusually long time rising to peak over at least 558… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Late-time TDE radio flares (Horesh et al 2021b;Goodwin et al 2022Goodwin et al , 2023bPerlman et al 2022;Cendes et al 2022Cendes et al , 2023Sfaradi et al 2022;Somalwar et al 2023;Christy et al 2024;Sfaradi et al 2024;Zhang et al 2024) are an intriguing part of the TDE puzzle. Some cases, notably AT2018hyz, show a very steep rise in late time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Late-time TDE radio flares (Horesh et al 2021b;Goodwin et al 2022Goodwin et al , 2023bPerlman et al 2022;Cendes et al 2022Cendes et al , 2023Sfaradi et al 2022;Somalwar et al 2023;Christy et al 2024;Sfaradi et al 2024;Zhang et al 2024) are an intriguing part of the TDE puzzle. Some cases, notably AT2018hyz, show a very steep rise in late time.…”
Section: Discussionmentioning
confidence: 99%
“…Following the surprising discovery of late radio emission from ASASSN-15oi (Horesh et al 2021a), numerous radio flares as late as ∼1000 days after the optical discoveries (Horesh et al 2021b;Cendes et al 2022Cendes et al , 2023Goodwin et al 2022Goodwin et al , 2023bPerlman et al 2022;Sfaradi et al 2022;Somalwar et al 2023;Christy et al 2024;Zhang et al 2024;Sfaradi et al 2024) have been observed. Recently Cendes et al (2023) reported that about 40% of optical TDEs are accompanied by late-time radio flares.…”
Section: Introductionmentioning
confidence: 99%